Metabolic Adaptation and Weight Regain Phenomenon After Cessation of GLP-1 Analogue Pharmacotherapy : A Review of Preventive Strategies - Babik, Karolina; Oliwia Bartkowska; Banatkiewicz, Joanna; Deka, Emilia; Domińczak, Jan; Czarnecka, Sofia; Łuczyńska, Gabriela; Dobosz, Adam; Wojnowski, Antoni; Bojanowska, Hanna Maria (Journal of Education, Health and Sport, 2026)
Obesity is currently recognized as a chronic, relapsing and progressive disease, constituting one of the most serious public health challenges of the 21st century. The introduction of glucagon-like peptide-1 receptor agonists (GLP-1 RAs), such as semaglutide and tirzepatide, has led to unprecedented therapeutic success, enabling weight reduction comparable to that achieved by bariatric surgery. However, despite their high efficacy, discontinuation of these agents is associated with rapid and clinically significant weight regain. The aim of this paper is to analyze the physiological mechanisms responsible for post-treatment weight regain following GLP-1 analogue withdrawal and to evaluate the effectiveness of selected strategies aimed at limiting this phenomenon, with particular emphasis on resistance training, nutritional interventions and pharmacological deprescribing models. Available clinical and experimental data indicate that weight regain is driven primarily by metabolic adaptation, including a disproportionate reduction in resting metabolic rate, loss of lean body mass and dysregulation of appetite-controlling hormones. Evidence from major clinical trials (STEP, SURMOUNT) confirms that up to two-thirds of the lost body weight may be regained within one year after cessation of therapy. The findings highlight the necessity of treating obesity pharmacotherapy as part of a long-term management strategy. Integration of pharmacological treatment with resistance training, high-protein dietary patterns and gradual dose reduction protocols appears essential for sustaining therapeutic effects and preventing the rebound phenomenon.